Validation of CP‐GEP (Merlin Assay) for predicting sentinel lymph node metastasis in primary cutaneous melanoma patients: A U.S. cohort study. (29th April 2021) - Yousaf, Ahmed; Tjien‐Fooh, Félicia J.; Rentroia‐Pacheco, Barbara; Quattrocchi, Enrica; Kobic, Ajdin; Tempel, Dennie; Kolodney, Michael; Meves, Alexander
Abstract: Background: Approximately 85% of melanoma patients who undergo a sentinel lymph node biopsy (SLNB) are node‐negative. Melanoma incidence is highest in patients ≥65 years, but their SLNB positivity rate is lower than in younger patients. CP‐GEP, a model combining clinicopathologic and gene expression variables, identifies primary cutaneous melanoma (CM) patients who may safely forgo SLNB due to their low risk for nodal metastasis. Here, we validate CP‐GEP in a U.S. melanoma patient cohort. Methods: A cohort of 208 adult patients with primary CM from the Mayo Clinic and West Virginia University was used. Patients were stratified according to their risk for nodal metastasis: CP‐GEP High Risk and CP‐GEP Low Risk. The main performance measures were SLNB reduction rate (RR) and negative predictive value (NPV). Results: SLNB positivity rate for the entire cohort was 21%. Most patients had a T1b (34%) or T2a (31%) melanoma. In the T1‐T2 group (153 patients), CP‐GEP achieved an SLNB RR of 41.8% (95% CI: 33.9‐50.1) at an NPV of 93.8% (95% CI: 84.8‐98.3). Subgroup analysis showed similar performance in T1‐T2 patients ≥65 years of age (51 patients; SLNB positivity rate, 9.8%): SLNB RR of 43.1% (95% CI: 29.3‐57.8) at an NPV of 95.5% (95% CI: 77.2‐99.9). Conclusion: We confirmed the potential of CP‐GEP to reduce negative SLNB in all relevant age groups. Our findings are especially relevant to patients ≥65 years, where surgery is often elective. CP‐GEP may guide SLNB decision‐making in clinical practice.